LEARNING OBSTACLES SISWA SEKOLAH MENENGAH PERTAMA PADA MATERI MATEMATIKA - Nadiatun Firda; Dadang Juandi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Mathematics has six material studies in the form of numbers, algebra, measurement, geometry, data analysis and probability, and calculus. This study aims to analyze the learning obstacles contained in each study of mathematics materials. The method used is Systematic Literature Review (SLR). From the Google Scholar database, 7,060 articles match the search string. The screening process based on the 2018-2022 range found 4,560 articles. And then, there are only 275 articles whose pdf is available, and 46 articles were from junior high school level. The last stage is that there are 13 journals that examine the three learning obstacles, such as ontogenic obstacles, epistemological obstacles, and didactical obstacles. No matching articles were found in the ERIC and Garuda databases. This article analyzed mathematics material and obtained learning obstacles from each study of the materials. Ontogenic obstacles are lack of motivation, student learning interest, and student readiness to learn, as well as short-term memory abilities, epistemological obstacles in the form of students' understanding of concepts and the use of formulas that are not yet appropriate, and didactic obstacles in the form of using teaching methods and materials that do not help students understand the material well.